Early morning irregularities detected with spaceborne GPS measurements in the topside ionosphere: A multisatellite case study - Zakharenkova, Irina (2015)
We present observations of the equatorial plasma bubbles (EPB) in the topside ionosphere at early morning hours (05–08 LT) in the recovery phase of the 18–19 February 2014 geomagnetic storm. This rare type of irregularities was detected in the Pacific sector using GPS measurements on board several low‐Earth‐orbit (LEO) satellites. We use a multisatellite constellation consisted of the three Swarm and one TerraSAR‐X satellites, that on 19 February flew in the same region and at similar altitudes ~500 km. The EPB occurrence in the LEO GPS data was observed for several consecutive orbits from ~11 UT to 16–17 UT on 19 February 2014, which suggests the following: (1) rather long duration (hours) of favorable conditions for EPB generation, (2) formation and evolution of EPB over wide longitude range of the Pacific Ocean, and (3) possible movement of the EPB region in the westward direction (with dawn). Registration of the early morning EPB in LEO GPS data was supported by concurrent in situ (Swarm and DMSP (Defense Meteorological Satellite Program)) and ground‐based (ionosonde and GPS) measurements. LEO‐based GPS technique is found to be essential and promising data source to study the topside EPB over regions with lack of the ground‐based facilities. In addition, we use the Prompt Penetration Model and the Thermosphere‐Ionosphere Electrodynamics Global Circulation Model (TIE‐GCM) to identify the possible mechanisms responsible for the observed phenomenon. The model simulation results indicate the occurrence of the zone with the enhanced vertical plasma drift (~40–45 m/s) owing to the disturbance dynamo action in the predawn/dawn sector during 09–17 UT.